Group‐Centered Leadership: Progression Over Time, Effectiveness, and Practices. Issue 1 (26th May 2021) - Perry, Chad; Cebulla, Andreas; Dick, Bob
Abstract : A person assigned to a leadership position can progress along two pathways over time: the leader‐centered or the group‐centered leadership pathways. Leader‐centered leadership is ego‐driven and hierarchical. There are two similar forms of the leader‐centered pathway: the regular and the psychopathic forms. The first form is the common, normal progression outlined by Keltner, whereas the second form is more rapid and is the form taken by leader‐centered leaders who have a genetic predisposition to psychopathy. Eventually, both forms of leaders encounter personal hubris. The current article explores how both forms of the leader‐centered pathway progress over time. In contrast, leaders progressing along the second leadership pathway are group‐centered and empathy‐driven and do not focus on themselves. Researchers have found that these group‐centered leaders are more effective than leader‐centered leaders. Because group‐centered leadership is so important, some of its characteristics have been described elsewhere and are extended upon here in a comprehensive account of the practices associated with the group‐centered leadership pathway. In conclusion, group‐centered leadership practices are critical to a group's effectiveness, and group‐centered leadership must be established when a group is initially formed.